Minimally invasive surgical treatment for sigmoid colon cancer in a patient with situs inversus totalis: a case report - Zhang, Chao-Yue; He, Jing; Huang, Lang-Chao; Chen, Long; Pan, Hui; Chen, Yong-Le; Peng, Yi (Frontiers in Oncology, 2025)
Situs inversus totalis (SIT) is a rare congenital condition characterized by a complete reversal of the internal organ arrangement, presenting significant surgical challenges. While previous cases of colorectal cancer in SIT patients have been reported, cases involving sigmoid colon cancer are sporadic. Here, we present the case of a 68-year-old female with sigmoid colon cancer and SIT. Following thorough preoperative preparation and a multidisciplinary team (MDT) consultation, the patient successfully underwent a laparoscopic radical sigmoidectomy. Her postoperative recovery was smooth, and she was discharged on postoperative day 10. At the 3-month follow-up, no short-term complications or signs of tumor recurrence were observed. This case highlights the importance of meticulous surgeon positioning in facilitating laparoscopic surgery for patients with SIT.